PENYELESAIAN HUKUM PENANGANAN KASUS GAGAL BAYAR PINJAMAN OLEH ANGGOTA KOPERASI SIMPAN PINJAM : Studi Kasus Putusan Pengadilan Negeri Kota Agung Nomor 3/Pdt.G/2021/PN Kot - gandis, ajeng; Prawesthi, Wahyu (UIR Press, 2024)
This study examines the roles of cooperative management, the supervisory board, and mediator judges in resolving loan default cases by savings and loan cooperative members. The study utilizes a case study approach, analyzing District Court of Kota Agung Decision No. 3/Pdt.G/2021/PN Kot Dated March 31, 2021. The findings highlight the central roles of cooperative management, the supervisory board, and mediator judges in resolving this case. Cooperative management bears the responsibility for initial handling and reporting issues to the supervisory board. When internal solutions are not reached, the mediator judge plays a crucial role in facilitating a peaceful settlement of the dispute before it proceeds to the judicial process for a final decision. The legal settlement steps taken in this case have followed the Standard Operating Procedure (SOP) in accordance with applicable regulations, effectively involving all three parties.